THE EFFECT OF ADVERTISING SPENDING ON BRAND LOYALTY MEDIATED BY STORE IMAGE, PERCEIVED QUALITY, AND BRAND TRUST. - Wisanggeni Bagus Anggoro (House of Management and Business (HOMBIS) Journal, 2022)
The purpose of this research was to analyze the effect of Advertising Spending on brand loyalty with store image, perceived quality, and brand trust as the mediating variables on Yamaha motorcycle on Purwokerto. The random sampling found 125 respondents and data was analyzed by Structural Equation Model (SEM). The result of this research confirmed that advertising spending has positive effect on brand loyalty, and store image, perceived quality, and brand trust mediates the effect between advertising spending and brand loyalty.The result of study shows that advertising spending has a value in building brand loyalty through store image, perceived quality, and brand trust, and sugests to the managers to increase the advertising through mass media and brand community.